Comment on Cheema U N, et al. (J Pak Med Assoc. 74: 1051-1054, June 2024) Film as an educational tool in medical pedagogy: A study on cinemeducation and its effectiveness - Thorakkal Shamim (Journal of the Pakistan Medical Association, 2025)
Dear Editor, I am addressing my notions on the researcharticle by Cheema UN et al. titled “Film as an educationaltool in medical pedagogy: A study on cinema educationand its effectiveness”. I found this paper to beenlightening and up to the minute.1The studyemphasises the importance of entertainment andlearning value of film as an educational tool in medicalpedagogy and it was conducted in medical students infourth and final year who are exposed to diverse medicaldisciplines such as family medicine,psychiatry,palliativecare and ethics with sound theoretical and practicalbrilliance.1 Moreover,a hospital based study on cinemaeducation on medical specialist group was made in Indiaby selecting motivational movies, biopics movies, andmovies related to healthcare available in various internetplatforms(over-the-top (OTT) media).2 Therefore, moreresearch to be initiated around the globe regardingcinema education in future and the followingformulations may be satisfied through cinema educationin medical pedagogy such as overcoming the challengesoutside their comfort zone, overcoming fear and anxietyin working setup, enhance cognitive and practicallearning master plan, empathy ,soft skills and behaviourmodification to generate productivity and creativity ofhealth professionals.1,2,3